PENYELESAIAN SENGKETA PERJANJIAN SEWA MENYEWA RUKO SECARA LISAN DI KELURAHAN BENAI (STUDI KASUS PERJANJIAN SEWA MEYEWA RUKO SECARA LISAN DI KABUPATEN KUANTAN SINGINGI) - Fiky Indra; Maryati Bachtiar; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Humans as social beings are creatures that are very dependent on oneanother because they are bound by the norms and values that exist in social life. The mainissues in this study are: How is the binding force of the shop rental agreement verballybetween the parties in Benai Village; and how to resolve a dispute over a shop leaseagreement orally between the parties in Benai Village.In the case raised by researchers in the existence of an agreement made inwriting or by carrying out an agreement verbally located in Kuantan Singingi Regency. Asdescribed in the implementation of the verbal agreement, this occurred in the people of BenaiSubdistrict, who could be said to be not backward from the Kuantan Singingi area, but whathappened illustrated the rise of spontaneous community interaction that occurred and wascarried out with awareness.The results of this study are: The strength of binding the rental agreement torent a shop orally in Benai Village, Benai District, Kuantan Regency carries out the leaseagreement verbally (not in writing) and the parties are still bound by mutual trust so that manydisputes arise, so that disputes that occur in Kelurahan This benai. Verbal settlement of leaseagreement disputes in Benai Village is carried out on the basis of the agreement of the partiesthat dispute resolution chosen out of court on the grounds of seeking resolution of the problemby the disputing parties is connected by each representative or relative of both to act as amediator in finding solutions to problems in a deliberation between the two as mediation of theparties with the result of a settlement based only on oral (non-written) testimony betweenrepresentatives of relatives present at the deliberation so that there is still the potential fordisputes to arise from the results of the deliberation.The authors, involved in resolving the dispute over the rental agreement forshophouses in Benai Village will be able to put the results of the deliberations in writing sothat later the settlement involves other authorized parties in supervising or monitoring theresults of deliberations between parties so that it can become a new way of solving problems inBenai Village.Keywords: Disputes-Lease-Oral Agreement.